Economia, sociedade e paisagens da capitania e comarca de Ilhéus no período colonial - Dias, Marcelo Henrique (2007)
This is an overview study on the formation of the land ownership structure in the colonial period at the old captaincy of Ilhéus. In the first part of the study, an analyses of the market is carryed out, focusing on the demanded products, the comercial circuits in the region, the trade with the rest of Portuguese America and even with localities over-seas, as well as commercial mechanisms. In the second part, the structures of land production, the areas of the incidence of cultivation and production, the routes of circulation of goods, and the use of wood warehouses (feitorias) are presented. It was concluded that the dinamics of economic spaces in the old Captaincy corresponds to the level of its commercial exchange with the economic centers responsible for demand and capital.